2011
DOI: 10.1186/1471-2164-12-148
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing and annotation of the microalgae Dunaliella tertiolecta: Pathway description and gene discovery for production of next-generation biofuels

Abstract: BackgroundBiodiesel or ethanol derived from lipids or starch produced by microalgae may overcome many of the sustainability challenges previously ascribed to petroleum-based fuels and first generation plant-based biofuels. The paucity of microalgae genome sequences, however, limits gene-based biofuel feedstock optimization studies. Here we describe the sequencing and de novo transcriptome assembly for the non-model microalgae species, Dunaliella tertiolecta, and identify pathways and genes of importance relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
161
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(173 citation statements)
references
References 69 publications
7
161
3
2
Order By: Relevance
“…The increase in total lipid content could be partially explained for a boost in transcript levels of genes encoding enzymes of the lipid biosynthesis pathways. According to this assumption, recent investigations showed that genes encoding the enzymes that catalyze the last step in the Kennedy pathway of triacylglycerol biosynthesis [81], such as glycerol-3-phosphate acyltransferase and acyl-glycerol-3-phosphate acyltransferase, are upregulated in response to nitrogen starvation [64,82,83]. Furthermore, the increase in total carbohydrate content can be explained by changes in the expression levels of genes involved in carbohydrate metabolism.…”
Section: Total Protein Total Lipid and Total Carbohydrate Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in total lipid content could be partially explained for a boost in transcript levels of genes encoding enzymes of the lipid biosynthesis pathways. According to this assumption, recent investigations showed that genes encoding the enzymes that catalyze the last step in the Kennedy pathway of triacylglycerol biosynthesis [81], such as glycerol-3-phosphate acyltransferase and acyl-glycerol-3-phosphate acyltransferase, are upregulated in response to nitrogen starvation [64,82,83]. Furthermore, the increase in total carbohydrate content can be explained by changes in the expression levels of genes involved in carbohydrate metabolism.…”
Section: Total Protein Total Lipid and Total Carbohydrate Contentmentioning
confidence: 99%
“…Furthermore, the increase in total carbohydrate content can be explained by changes in the expression levels of genes involved in carbohydrate metabolism. For example, when the oleaginous microalgae Neochloris oleoabundans is cultured under nitrogen starvation, the catabolic phase of starch, specifically α-amylase, which hydrolyzes starch to glucose, is strongly repressed [83]. …”
Section: Total Protein Total Lipid and Total Carbohydrate Contentmentioning
confidence: 99%
“…It is pertinent to note here that, despite the aforementioned progress in algal genomics, the rationale for sequencing these algal strains was not in the context of their lipid synthesis and hence, there still remains a paucity of biofuel-relevant genomic information (Blankenship, 2010;Rismani-Yazdi et al, 2011). The recently reported endeavours in algal transcriptome profiling have successfully demonstrated the feasibility of bypassing the bottleneck of genome sequencing and have improved our understanding of lipid metabolism in some unsequenced oleaginous microalgal species (Guarnieri et al, 2011;Rismani-Yazdi et al, 2011).…”
Section: Agrigenomics For Microalgal Biofuelmentioning
confidence: 99%
“…Each micro-environment may provide algae strains with very different properties. As opposed to only manipulating a few individual cultured algae strains in the laboratory for high lipid productivity, a more efficient and useful strategy to identify oleaginous microalgae would be an in-depth and systematic investigation of a whole taxonomic group of microalgae over a wide geographical and ecological distribution [20]. By correlating this with algal oil contents and optimal environmental growth conditions, a predictive tool for selecting optimal microalgae strains for biofuel production maybe developed.…”
Section: Sampling and Isolation Of Pure Culturesmentioning
confidence: 99%